Task reformulation as a practical tool for formation of electronic digest of tasks - Minďáková, Ingrid; Šveda, Dušan (Teaching Mathematics and Computer Science, 2007)
Creative thinking as well as thinking itself is being developed at active learning-cognitive activity of students. To make mathematic matter a subject of interest and work of students at classes, it is efficacious to submit it in a form of tasks. The tasks may be set up in a purposeful system of tasks by means of which reaching the teaching goals in the sense of quality and durability of gained knowledge may be more effective. A suitable means for presentation of tasks with their characteristics (as e.g. didactic function and cognitive level) as well as task systems themselves is an electronic digest of tasks as a database. The analysis of textbooks and digests of tasks commonly used at schools in Slovakia shows that they do not include all the types of tasks necessary for setting up complete (in the sense of didactic functions) task systems. One of the most important methods used for formation of the missing tasks is reformulation of tasks. The individual strategies of task reformulation are explained in details on examples in this article.